Membraneless Organelles and Condensates Orchestrate Innate Immunity Against Viruses - Boccaccio, Graciela Lidia (2023)
The cellular defense against viruses involves the assembly of oligomers, granules and membraneless organelles (MLOs) that govern the activation of several arms of the innate immune response. Upon interaction with specific pathogen-derived ligands, a number of pattern recognition receptors (PRRs) undergo phase-separation thus triggering downstream signaling pathways. Among other relevant condensates, inflammasomes, apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC) specks, cyclic GMP-AMP synthase (cGAS) foci, protein kinase R (PKR) clusters, ribonuclease L-induced bodies (RLBs), stress granules (SGs), processing bodies (PBs) and promyelocytic leukemia protein nuclear bodies (PML NBs) play different roles in the immune response. In turn, viruses have evolved diverse strategies to evade the host defense. Viral DNA or RNA, as well as viral proteases or proteins carrying intrinsically disordered regions may interfere with condensate formation and function in multiple ways. In this review we discuss current and hypothetical mechanisms of viral escape that involve the disassembly, repurposing, or inactivation of membraneless condensates that govern innate immunity. We summarize emerging interconnections between these diverse condensates that ultimately determine the cellular outcome.